Gender and Ethnic Disparities of Acute Kidney Injury in COVID-19 Infected Patients: A Literature Review - He, Weihang; Liu, Xiaoqiang; Hu, Bing; Li, Dongshui; Chen, Luyao; Li, Yu; Zhu, Ke; Tu, Yechao; Xiong, Situ; Wang, Gongxian; Fu, Bin (Frontiers in Cellular and Infection Microbiology, 2022)
The novel coronavirus (SARS-CoV-2) has become a life-threatening pandemic. Clinical evidence suggests that kidney involvement is frequent, ranging from mild proteinuria to advanced acute kidney injury (AKI). Moreover, AKI may affect >20% of hospitalized patients with coronavirus disease 2019 (COVID-19) and >50% of patients with COVID-19 in the ICU. COVID-19‐induced kidney injury is affected by several factors, including the direct action of the virus in the renal parenchyma mediated by binding to angiotensin-converting enzyme 2, the immune response dysregulation, and cytokine storm driven by SARS-CoV-2 infection, organ interactions, hypercoagulable state, and endothelial dysfunction. Data from China and the United States showed that male sex, the elderly, Black race, diabetes, chronic kidney disease, hypertension, cardiovascular disease, and higher body mass index are associated with COVID-19‐induced AKI. In this review, we found gender and ethnic differences in the occurrence and development of AKI in patients with COVID-19 through literature search and analysis. By summarizing the mechanism of gender and ethnic differences in AKI among patients with COVID-19, we found that male and Black race have more progress to COVID-19-induced AKI than their counterparts.